International neuromonitoring study group guidelines 2018: Part II: Optimal recurrent laryngeal nerve management for invasive thyroid cancer—incorporation of surgical, laryngeal, and neural electrophysiologic data. (6th October 2018) - Wu, Che‐Wei; Dionigi, Gianlorenzo; Barczynski, Marcin; Chiang, Feng‐Yu; Dralle, Henning; Schneider, Rick; Al‐Quaryshi, Zaid; Angelos, Peter; Brauckhoff, Katrin; Brooks, Jennifer A.; Cernea, Claudio R.; Chaplin, John; et al.
Abstract : The purpose of this publication was to inform surgeons as to the modern state‐of‐the‐art evidence‐based guidelines for management of the recurrent laryngeal nerve invaded by malignancy through blending the domains of 1) surgical intraoperative information, 2) preoperative glottic function, and 3) intraoperative real‐time electrophysiologic information. These guidelines generated by the International Neural Monitoring Study Group (INMSG) are envisioned to assist the clinical decision‐making process involved in recurrent laryngeal nerve management during thyroid surgery by incorporating the important information domains of not only gross surgical findings but also intraoperative recurrent laryngeal nerve functional status and preoperative laryngoscopy findings. These guidelines are presented mainly through algorithmic workflow diagrams for convenience and the ease of application. These guidelines are published in conjunction with the INMSG Guidelines Part I: Staging Bilateral Thyroid Surgery With Monitoring Loss of Signal. Level of Evidence: 5 Laryngoscope, 128:S18–S27, 2018